GOODS ON DELIVERY SYSTEM ADMINISTRATION IN PT.RAHMAT USING MICROSOFT VISUAL BASIC 6.0 - YUDHI RENUR; Aqwam Rosadi Kardian, SKom., MM Aqwam Rosadi Kardian, SKom., MM (Jurnal Sistem Informasi, 2008)
The development of increasingly sophisticated computer that is very helpful in dataprocessing still using manual systems. This is often meninbulkan issues related to theaccuracy of the data which resulted in delays in data processing.Valuable information is the information quickly and accurately. Then needed acomputerized system as a supporter. Service delivery system is designed with the aim tosimplify the processing of data and preparing reports.